Development of ZnO/Ag Nanocomposite Film for Gas Sensing Application - Davis, Deepak; Singh, Sheela (Asian Journal of Chemistry, 2017)
The sol-gel technique was used to prepare zinc oxide nanoparticles doped with silver ions. The sample phase and microstructure were characterized by different techniques such as X-ray diffraction, field emission scanning electron microscopy, also absorption and metal composition were finding by UV-visible spectra, EDAX, respectively. In this paper, we tried with ZnO/Ag nanocomposite with pH 9 and varying the composition of silver ions. X-ray diffraction study showed that increasing in intensity of silver with the silver concentration, which indicates the formation of ZnO/Ag composite. The prepared sample maintains the good morphology and microstructure of pure ZnO. Sensing results showing that ZnO/Ag nanocomposite shows better sensing properties. 5 wt % AgNO3 and 0.5 g of ZnO with adding 1 mol NaBH4 in 5 mL of ZnO/Ag composite (pH 9) were giving better sensing output. The fabricated device showed that high sensor response of 72 % at 1000 ppm and the low detection limit is 5 ppm.